Peran Guru dalam Meningkatkan Minat Belajar Matematika di SD/MI - Kenes Dian Maharyati; Noor Thania; Nofita Lusiana; Dian Mustika Anggraini (IEC: Journal of Educational Innovation, 2026)
This study aims to analyze the role of teachers in increasing students' interest in learning mathematics in elementary/middle school through a literature review. The method used is a literature study by examining various scientific articles, books, and relevant sources related to the role of teachers and the interest in learning mathematics of elementary school students. The results of the study show that teachers have an important role as facilitators, motivators, and evaluators in the learning process. As facilitators, teachers provide a conducive learning environment and interesting learning media. As motivators, teachers provide encouragement, rewards, and guidance that can increase students' enthusiasm for learning. As an evaluator, teachers conduct assessments to find out the progress of student learning, as well as improve the learning strategies used. Therefore, optimizing the role of teachers is an important factor in increasing students' interest in learning mathematics in elementary/middle school. The results of this study show that the role of teachers as motivators in increasing students' learning interest is to provide motivation in the form of advice, reprimands, and haidah. The role of teachers is to support students in improving their way of learning. Teachers also provide facilities such as comfortable, safe, and clean classrooms.